2010
DOI: 10.1115/1.4002317
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Structural Stiffness and Energy Dissipation Parameters in a Second Generation Foil Bearing: Effect of Shaft Temperature

Abstract: Established high temperature operation of gas foil bearings (GFB) is of great interest for gas turbine applications. The effects of (high) shaft temperature on the structural stiffness and mechanical energy dissipation parameters of a foil bearing (FB) must be assessed experimentally. Presently, a hollow shaft warmed by an electric heater holds a fioating second generation FB that is loaded dynamically by an electromagnetic shaker. In te.sts with the shaft temperature up to 184°C, the measurements of dynamic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 20 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…Measurements from a series of (applied static) load versus displacement (due to WMD deflection) aid to determine the forced performance of the test WMDs. Note that the static load-deflection test offers substantial savings in cost and time to determine the energy dissipation characteristics of mechanical components with compliant structures since the identified structural parameters from the area inside the hysteresis loop of the static load versus the deflection curve show remarkable agreement with those obtained from dynamic load tests (at low excitation frequency, in particular) [28,29]. The current study presents average values of the identified parameters from three non-sequential and independent measurements of push-pull loads and WMD displacements.…”
Section: Identification Procedures Of Wmd Structural Stiffness and Dammentioning
confidence: 71%
“…Measurements from a series of (applied static) load versus displacement (due to WMD deflection) aid to determine the forced performance of the test WMDs. Note that the static load-deflection test offers substantial savings in cost and time to determine the energy dissipation characteristics of mechanical components with compliant structures since the identified structural parameters from the area inside the hysteresis loop of the static load versus the deflection curve show remarkable agreement with those obtained from dynamic load tests (at low excitation frequency, in particular) [28,29]. The current study presents average values of the identified parameters from three non-sequential and independent measurements of push-pull loads and WMD displacements.…”
Section: Identification Procedures Of Wmd Structural Stiffness and Dammentioning
confidence: 71%
“…In FBs, Coulomb-type damping (dry friction) arises due to the relative motions between the bumps and the top foil, and between the bumps and the bearing cartridge ID, see Ref. [24].…”
Section: Prediction Of Rotor Imbalance Responses and Comparisonmentioning
confidence: 99%
“…14 [38]. Recall that the static load-FB deflection measurements substantially decrease the time and cost in evaluating the mechanical energy dissipation characteristic of bump-type foil bearings [39]. The procedure for the current experiments is to 1) Affix the motor support housing on the rig base plate.…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%
“…In FBs, Coulomb-type damping (dry friction) arises due to the relative motions between the bumps and the top foil, and between the bumps and the bearing cartridge ID, see Ref. [39]. in the housing enclosure (T e -T amb ) versus air cooling flow rate for test cases#1 and #3.…”
mentioning
confidence: 99%